Characterization of vegetation structure in areas of natural occurrence of Hancornia speciosa Gomes - dos Reis, Régilla Martins (2021)
The mangabeira (Hancornia speciosa Gomes) has great food and pharmaceutical values but its production is almost entirely made by people gathering fruits in forests, which increases the risk extinction, particularly in savannah regions. Thus, the objective of this study was to compare floristic, phytosociology and species diversity in five areas of natural occurrence of mangabeira. All plants with a diameter at soil level equal to or greater than five cm were selected by the quadrant method in five villages in the state of Maranhão, northeastern Brazil. The assessed variables for the whole vegetation were number of individuals, number of species, total density, the Shannon Diversity Index (H′), the Jaccard Similarity Index, total plant height and diameter at soil level. The phytosociological parameters computed for the mangabeira population were absolute and relative density, frequency and dominance; basal area, importance value and cover value. We recorded 1,696 plants from 26 species and 16 families. Anacardiaceae, Apocynaceae and Fabaceae were the families that stood out most with two species each. The species diversity was low in all villages, varying from H′= 0.659 in Santana to H′ = 1.777 in Recanto. The floristic similarity among the vegetation in all villages was low except between Patizal and Recurso (0.571). For the mangabeira population, the importance value and cover value were higher in Santana, with 79.35% and 85.28% respectively and the highest values of plant height (6.02 meters) and diameter at soil level (13.76 cm) were found in Patizal village. These results could be used for management, preservation and sustainability of the mangabeira in northeastern Brazil.